2019
DOI: 10.1021/acs.inorgchem.9b01159
|View full text |Cite
|
Sign up to set email alerts
|

Two-Coordinate, Late First-Row Transition Metal Amido Derivatives of the Bulky Ligand -N(SiPri3)Dipp (Dipp = 2,6-diisopropylphenyl): Effects of the Ligand on the Stability of Two-Coordinate Copper(II) Complexes

Abstract: The synthesis and spectroscopic, structural, and magnetic characterization of the quasi-linear metal­(II) bis­(amides) M­{N­(SiPr i 3)­Dipp}2 [Dipp = C6H3-2,6-Pr i 3; M = Fe (1), Co (2), or Zn (3)] are described. The magnetic data demonstrate the impact of metal ligand π-interactions on the magnetic properties of these two-coordinate transition metal amides. Disproportionation of the copper­(I) amide species featuring the ligand -N­(SiPr i 3)­Dipp resulted in the decomposition product [(Pr i 3Si)­N­(c-C6H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The impact of attracting intramolecular dispersion interactions is further discussed to influence M-N distances. 12,22 However, the cobalt complexes 4 (M = Fe (8), Co (9), L 2 = N(Dipp)SiMe 3 ).…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…The impact of attracting intramolecular dispersion interactions is further discussed to influence M-N distances. 12,22 However, the cobalt complexes 4 (M = Fe (8), Co (9), L 2 = N(Dipp)SiMe 3 ).…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…The Power group reported on another attempt to generate dicoordinate Cu II complexes in 2019 when they employed modified variants of the aryl(silyl)amide of the 2016 study [21] . However, while for both Cu{N(Si i Pr 3 ) 2 Dipp} 2 ( C ) and Cu{N(Si i Pr 3 )Dipp‐4‐Ad} 2 ( D ) unambiguous EPR spectra were obtained and the characteristic blue colour of the dicoordinate Cu II complexes was observed, the isolation of the complexes was not possible due to their thermal instability.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, this research group demonstrated the versatility of the amido ligand [N­(Si i Pr 3 )­DIPP] (DIPP = 2,6-di- iso -propylphenyl) in supporting two-coordinate chromium complexes in the +1, +2, and +3 oxidation states, as well as the two-coordinate vanadium­(II) complex D (Scheme ). Other groups have used this amido ligand with yttrium, alkaline earth metals, and several late transition metals . Further investigations of this bulky amido ligand in allowing access to low-valent early transition metal complexes are described here, involving the synthesis, characterization, and reactivity of a family of low-coordinate, heteroleptic complexes of titanium­(III) supported by the [N­(Si i Pr 3 )­DIPP] ligand.…”
Section: Introductionmentioning
confidence: 99%
“…20 Other groups have used this amido ligand with yttrium, 21 alkaline earth metals, 22−24 and several late transition metals. 25 Further investigations of this bulky amido ligand in allowing access to low-valent early transition metal complexes are described here, involving the synthesis, characterization, and reactivity of a family of low-coordinate, heteroleptic complexes of titanium-(III) supported by the [N(Si i Pr 3 )DIPP] ligand.…”
Section: ■ Introductionmentioning
confidence: 99%